Profil Mikrobiota Saluran Cerna Pada Anak, Dewasa, Berbagai Suku dan Ras - Dzulfachri Kurniawan; Armanto Makmun; Zulfahmidah Zulfahmidah; Windy Nurul Aisyah (Indonesian Journal of Health, 2020)
Background and Purpose: Microbiota is defined as a collection of microorganisms that live in the host's body, which can consist of bacteria, archae, viruses, and other eukaryotes. Microbiota in humans is also found in the skin, lungs, urinary tract, oral cavity, although the digestive tract plays a role in contributing to the highest number of microbiota in humans. The purpose of this article is to provide an overview of the various profiles of the gastrointestinal microbiota in children, adults, various ethnicities and races. Methods: This study uses a narrative review method. The data sources of this study come from literature obtained via the internet in the form of research results from national and international journals in 2010-2020 such as Elsevier, Clinical Key, Pubmed, Biomed Research International, Nature Journal, PLOS Computational Biology, PNAS Journal dan American Society For Microbiology. Results: From several collections of journals related to microbiota, many studies reveal that the two bacterial phyla Firmicutes and Bacteroidetes are found in a higher proportion in humans in general followed by Prevotella, Actinobacteria and Bifidobacterium. Whereas in children the microbiota is more dominated by Bacteroidetes / Bifidobacterium and not a few studies have found Clostridium in children. It is no different from ethnicities and races from other countries in that the findings of general microbiota are almost the same. Various microbiota also can be built from the environment, geography, ethnicity and culture. Conclusion: The variability of the microbiota in the human tract is very diverse, it is related to various factors, namely age, genetics, metabolic, diet, diet, lifestyle, environment, geography, ethnicity, culture and socio-economy.